Oat polar lipids and sunflower lecithin similarly improve cardiometabolic risk markers and appetite controlling hormone responses after breakfast and a subsequent lunch. A randomized crossover study in healthy adults - Hossain, Mohammad Mukul; Tovar, Juscelino; Cloetens, Lieselotte; de Kam, Soraya; Nilsson, Anne (Frontiers in Nutrition, 2024)
The alarming global increase in lifestyle-related disorders such as obesity and type 2 diabetes mellitus (T2DM) has increased during the last several decades. Poor dietary choices significantly contribute to this increase and prevention measures are urgently needed.Dietary intake of bioactive compounds found in foods are linked to a decrease likelihood of these disorders. For this purpose, a randomized crossover meal study was performed to compare the postprandial metabolic effects of lecithin and oat polar lipids in healthy subjects.Eighteen young healthy subjects ingested test meals enriched with lecithin, oat polar lipids (PLs) or rapeseed oil. There were four test meals i) 15 g oat polar lipids: OPL, ii) 18 g sunflower lecithin (of which 15 g were polar lipids): LPL, iii) 18 g rapeseed oil: RSO, and iv) reference white wheat bread: WWB. Lipid-enriched test meals contained equivalent amounts of total fat (18 g), and all breakfast meals contained 50 g available carbohydrates. The meals were served as breakfast followed by a standardised lunch (white wheat bread and meat balls) after 3.5 hours. Test variables were measured at fasting and repeatedly during 5.5 hours after ingestion of the breakfast.Results: Our study demonstrated that both LPL and OPL had beneficial effects on postprandial glucose and insulin responses, and appetite regulating gut hormones, as compared to RSO and WWB. Significant increase in GLP-1, GIP, and PYY concentrations were seen after consuming breakfast meals with LPL and OPL, and ghrelin concentration was reduced compared to meals with RSO and WWB (P < 0.05). Furthermore, triglycerides (TG) concentration was significantly reduced after OPL compared to RSO (P < 0.05). Our data show that there were no significant variations in glycaemic and insulin responses, TG, and gut hormone concentrations between LPL and OPL during breakfast (0-210 min) or over the whole study period (0-330 min).Our study revealed that the consumption of both lecithin and oat PLs included in breakfast meal may similarly enhance postprandial glucose tolerance, reduce TG, and enhance the secretion of incretins and appetite regulating hormones in healthy young adults.The study is registered at ClinicalTrials.gov (NCT05139355).